The effect of mowing and pasturing on grassland vegetation in Mátra Mauntains (Parádóhuta) - Pápay, Gergely; Péter, Norbert; Penksza, Károly (Gyepgazdálkodási Közlemények, 2021)
We carried out our surveys on grasslands near Parádóhuta. The sample area was a mountain grassland (Festucetum rubrae-Cynosuretum Tx. 1940, Soó 1957), which was mowed until 2013, then foraged with borzderes and racka cattle within the framework of nature conservation management for two years, and after that it became mowed again. We analysed the effects of foraging and mowing between 2013 and 2019.Our goals were the following: to disclose the vegetation of the sample areas (i), surveying the natural regeneration of the grassland and analysing, valuing the effect of mowing and foraging on grasslands (ii); analysing the vegetation in terms of nature conservation and valuing its life form spectrum (iii).The analysed grassland was very diverse in 2013, we noticed well differentiated Nardus stricta patches. In 2015 the vegetation became more mosaic-like because of heavy pasturing: animals have grazed arboreals and Nardus in lesser amount, but species diversity declined and coverage of shrub remained the same. In the last years of the survey foraging stopped, and mowing began, which increased the coverage of herbaceous plants, which approximated the values of the first years. According to our results, on these habitats systematic mowing has a much more positive effect on biodiversity and coverage of species marking naturalness.